ACTR-59. IMPROVING THE INTRA-OPERATIVE DIAGNOSIS OF HIGH-GRADE GLIOMA USING A FLUORESCENCE BIOMARKER – RESULT OF THE GALA-BIDD STUDY. (5th November 2018) - Watts, Colin; Ashkan, Keyoumars; Jenkinson, Michael; Kurian, Kathreena; Qian, Wendi; Price, Stephen; Matys, Tomasz; Doughton, Gail; Machin, Andrea; Jung, Josephine; Jalloh, Ibrahim; Harman, Chloe; et al.
Abstract: BACKGROUND: Correctly distinguishing gliomas as low or high grade (LGG or HGG) during surgery can influence the surgical procedure, enhancing resection and improving survival. The UK NCRI GALA-BIDD study was designed to prospectively investigate whether the presence of visible fluorescence is a pragmatic intra-operative diagnostic surgical biomarker of high-grade disease within a tumour mass in real time during surgery. METHODS: Patients with suspected intrinsic glioma discussed at neuro-oncology Multidisciplinary Team meetings and suitable for fluorescence guided cytoreductive surgery were eligible. 5-aminolevulinic acid (5-ALA) was used to generate visible fluorescence. Samples of fluorescent tissue were sent for peri-operative histopathological analysis to establish an intra-operative diagnosis of LGG or HGG. These data were compared with the final central pathological diagnosis. RESULTS: From Feb 2015 to March 2017 in the UK, 106 patients were recruited: median age 59 (range 23–77); 59% male; 25% WHO radiological grade II transforming to a higher grade and 55% grade IV. 5-ALA were given for 103 patients with a median dose of 1500mg (range 960-2200mg). 67% of patients classified as HGG at local peri-operative diagnosis were confirmed by the central review (weighted Kappa 0.37 (95%CI=0.21–0.54)). 88 patients were evaluable for the primary endpoint: 81 had visible fluorescence of the tumour with central histopathology diagnosis as 1 LGG, 78 HGG (a 99% concordance in HGG classification with the 99%CI=91%-99.9%) and 2 not assessed; 7 patients had no visible fluorescence and were diagnosed as 6 LGG and 1 HGG. CONCLUSION: There is an urgent need to improve the local peri-operative diagnosis. The presence of visible fluorescence can be used as an additional pragmatic intra-operative diagnostic surgical biomarker of high-grade disease within a tumour mass. Use for assessment of low-grade disease needs further investigation.